2011
DOI: 10.3136/fstr.17.251
|View full text |Cite
|
Sign up to set email alerts
|

Hinokitiol Inhibits Polyphenol Oxidase and Enzymatic Browning

Abstract: We screened for inhibitors of enzymatic browning among fermented broths of lactic acid bacteria (58 strains), extracts of spices (7 samples), and food additives (34 samples) from the standpoint of practical use. We found that hinokitiol, a preservative, definitely inhibited the browning of apple sections. An apple section sprayed with a 0.02% hinokitiol solution did not turn brown for 2 h at room temperature. Hinokitiol competitively inhibited apple polyphenol oxidase (PPO). The Ki value of hinokitiol against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For PPO assay, the reaction mixture consisted of 50 μL enzyme extract, 200 μL of 10 mM L-β-(3,4-Dihydroxyphenyl) alanine (L-DOPA) , and 750 μL of diluted Macilvain buffer (pH 4.5) . PPO activity was measured by increase in absorbance at 475 nm according to a modified method of Okumura et al (2011) and determined as change in absorbance at 475 nm/min/g fresh weight.…”
Section: Methodsmentioning
confidence: 99%
“…For PPO assay, the reaction mixture consisted of 50 μL enzyme extract, 200 μL of 10 mM L-β-(3,4-Dihydroxyphenyl) alanine (L-DOPA) , and 750 μL of diluted Macilvain buffer (pH 4.5) . PPO activity was measured by increase in absorbance at 475 nm according to a modified method of Okumura et al (2011) and determined as change in absorbance at 475 nm/min/g fresh weight.…”
Section: Methodsmentioning
confidence: 99%
“…Broothaerts et al (2000) showed that polyphenol oxidase reaction in transgenic apple and tobacco leaves was strongly inhibited by tropolone, a Cu competitor, and restored by the addition of Cu 2+ . Okumura et al (2011) found that hinokitiol (ß-thujaplicin) and tropolone definitely inhibited polyphenol oxidase and browning of apple sections and inhibited browning of shrimps (Penaeus indicus). For darkening or discoloration of shrimps during cold storage, tyrosinase is mainly responsible.…”
Section: And Polyphenol Oxidase Activitymentioning
confidence: 99%
“…Hinokitiol fresh sheets and hinokitiol dissolved in ethanol were used to prevent the decay of commercially harvested peaches, in which hinokitiol fresh sheets were more effective than hinokitiol dissolved in ethanol, and 41.1% of the untreated fruit developed brown rot . Hinokitiol used as an inhibitor for enzymatic browning of apples, apple sections sprayed with a 0.02% hinokitiol solution completely inhibited polyphenol oxidase and prevented browning . Hinokitiol inhibits ethylene production through suppression of ACC synthase and ACC oxidase in wounded winter squash mesocarps, apple fruit plugs, and peach seeds .…”
Section: Introductionmentioning
confidence: 99%
“…12 Hinokitiol used as an inhibitor for enzymatic browning of apples, apple sections sprayed with a 0.02% hinokitiol solution completely inhibited polyphenol oxidase and prevented browning. 13 Hinokitiol inhibits ethylene production through suppression of ACC synthase and ACC oxidase in wounded winter squash mesocarps, apple fruit plugs, and peach seeds. [14][15][16] Hence, the objective of the present investigation was to compare the effect of hinokitiol impregnated into nonwoven rayon on quality and shelf life extension of "KEK-1" tomatoes at two different temperatures (15°C and 25°C) under MAP and non-MAP conditions.…”
Section: Introductionmentioning
confidence: 99%